Hydrolysis of Phospholipids in Presence of Phospholipase D: Thrmodynamic and Kinetic Studies of Hydrolysis in Water and Alcoholic Environments - S. Hussein, Ikram; M. M. Al-Rammahi, Thaer (Al-Nahrain Journal of Science, 2024)
Phospholipase D (PLD) catalyzes the hydrolysis of phospholipids to produce phosphatidic acid and hydroxyl compounds. Phosphatidylcholine (PC) is the most abundant phospholipid in animals and plants, often constituting nearly 50% of total complex lipids in animals and plants. However, Phosphatidylserine (PS) makes up around 5–10% of all phospholipids. This work includes the monitoring thermodynamics and kinetics of the enzymatic hydrolysis of PC and PS in both water and ethanol. All experiments were performed using the Schlink line technique in N2 present as an inert gas to prevent the oxidative stress. UV/Vis. spectrophotometer was used to observe the kinetic of all enzymatic reactions. In addition, the Origin 2019 software was used to analyze and find the kinetic parameters of the enzymatic hydrolysis reactions. The results show that the enzymatic hydrolysis reactions of PC in water and in ethanol occurred at the same conditions, enzymatic activity 1.752 U/mg, temperature 37 ᵒC, and pH =7. However, the enzymatic hydrolysis reactions of PS in water occurred at different conditions than in ethanol. The enzymatic substitution reaction of PS in ethanol was thermodynamic favorable reaction due to the value of the ∆G = _164.868 J, but in water was thermodynamically unfavorable ΔG = 65.048 J. However, the enzymatic hydrolysis reaction of PC in water was thermodynamically unfavorable ∆G = 345.319 J as well as in ethanol ∆G = 74.433 J.  The study shows that there is a clear impact of presentitrogen bases of PC and the environment of the hydrolysis on the activity of the enzymatic catalyzing.